Effects of adhesion failure on moisture damage of warm mix asphalt containing cecabase additive - Kakar, Muhammad Rafiq Khan (2015)
Warm Mix Asphalt (WMA) is a technology that allows significant reduction in mixing and compaction temperatures of conventional hot mix asphalt. It is a cost effective technology that can improve mixture workability, reduces greenhouse gas emissions, and is environmental friendly. However, WMA is susceptible to moisture damage due to its lower production temperature. This can cause adhesion failure, hence stripping of asphalt binder from the aggregates. In this research, Cecabase warm mix additive was used to lower the production temperature and enhance the asphalt binder adhesion properties with aggregate. Two binders, PG-64 and PG-76, were used to prepare the test specimens. As a surfactant and when blended with asphalt binder, Cecabase promotes adhesion at the binder-aggregate interface. Therefore, the overall laboratory test results showed that addition of Cecabase had no significant effects on binder rheology and optimum binder content. A novel approach using image analysis was used to measure the asphalt mixture adhesion failure susceptibility due to moisture damage. The results showed that adhesion failure increased with the number of freeze and thaw cycles and mixtures prepared with PG-76 binder exhibited lower adhesion failure compared to PG-64 binder. To assess the adhesion failure, binder-aggregate substrate direct tensile and pull-off tension tests were carried out. An accelerated laboratory vacuum saturator (ALVS) moisture conditioning was fabricated to condition the binder-aggregate specimens. The results indicated that short term and long term aged binders when subjected to ALVS, were susceptible to moisture damage. In order to gain fundamental insight, the Surface Free Energy (SFE) of Cecabase-modified binder was evaluated using contact angle Goniometer and dynamic Wilhelmy plate device. The analytical measurements based on SFE results showed that Cecabase improved the spreadibility of asphalt binder over the limestone aggregate particles. In addition, the work of adhesion improved with the addition of Cecabase. The compatibility ratio is an indicator of moisture susceptibility and indicated that the granite aggregates were less resistant to moisture damage compared to limestone aggregates.